Ewangelicy we wschodnim rejonie Królestwa Polskiego - Jemielity, Witold (Prawo Kanoniczne, 2003)
The work concerns Augsburg and Reformed Protestants living on the area of the Augustów voivodship, which after the January Uprise was changed into Łomża and Suwałki guberniyas. After settling religious centres in the 40s of the nineteenth century the were nine parishes and eight branches on this area; there was only one Parish of the Protestant Church, while the rest of them were of Augsburg Protestant Church. There were over forty thousand Protestants at that time; about five hundred of them belonged to the Reformed Church. Protestants lived mainly on the area frontier line of the Congress Kingdom of Poland and Prussia ever since. Moreover, newly come German settlers lived on the area of Mazovia. On the eastern area of the Augustów voivodship lots of Protestants did not know German language and they used to pray in their native Lithuanian language. They mostly worked as farmers, though they also lived in the towns which were mostly inhabited by the followers of Moses. After the first World War eleven Parishes and branches were on the area of Lithuania while six of them were left in Poland. During that war the Russians deported lots of German settlers of their country and during the World War II numerous Protestants left for Germany. Protestants used to live among Roman-catholics, Orthodox and followers of Moses. During the first half of the century, before they regulated their own network of Parish Churches, Protestants baptised their children and got married in Roman-catholic churches and burried the deceased on the area of common cementaries. The problem of the mixed marriages was not regulated, as a rule the priest of the fiancée should give his blessing. After the January Uprise the Ortodox moved to the above described area. They were protected by the government. However the followers of Moses created a great but closed social and religious group.